2017
DOI: 10.1113/ep086265
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous physical activity and mediators of energy homeostasis in the hypothalamus of mice from 4 to 10 months of age

Abstract: What is the central question of this study? Is the initial decline of spontaneous physical activity (SPA) in mice related to impaired insulin and leptin signalling or brain-derived neurotrophic factor expression in the hypothalamus? What is the main finding and its importance? We showed that SPA started to decline at an early stage, concomitantly with an impairment of hypothalamic leptin signalling. Consequently, energy expenditure decreased and glucose tolerance worsened. Our results demonstrate the need to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…During normal ageing, locomotor activity declines with progressive body weight gain [25][26][27], indicating that physical activity is an important health factor [28]. In this regard, laboratory mice have lifelong food availability and generally a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…During normal ageing, locomotor activity declines with progressive body weight gain [25][26][27], indicating that physical activity is an important health factor [28]. In this regard, laboratory mice have lifelong food availability and generally a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated the effects of long-term social isolation on metabolic, behavioural, and central nervous system-related areas in middle-aged mice. This is a period of life characterized by the beginning of some age-related metabolic and behavioural alterations [25] , [26] , [27] , [28] , thus being particularly important but yet not so explored. Our main finding was that long-term social isolation can impair short-term memory, which was associated with a decrease in ΔFosB and BDNF expression at hippocampal DG and CA3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known on how long-term social isolation can affect a mature and developed mouse, especially when they reach middle age, a period in which some age-related metabolic and behavioural alterations start to manifest [25] , [26] , [27] . We have shown that middle-aged mice displayed decreased locomotor activity and impaired glucose tolerance [28] , while others have demonstrated a decline in cognitive function as a result of hyperglycemia [29] . Indeed, the decline in cognitive parameters during aging can be explained by an increase in oxidative stress [30] and a decrease in neurotrophins, like brain-derived neurotrophic factor (BDNF) [31] .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For rodents, all activity in a home cage, mostly in the form of locomotion and rearing behaviours, is considered physical activity. To date, some determinants of home‐cage activity have been identified, such as a high‐fat diet (Bjursell et al., 2008; Moretto et al., 2017), calorie restriction (Teske & Kotz, 2009), psychosocial stress (Bartolomucci et al., 2003) and ageing (Benfato et al., 2017). Few studies have investigated how social isolation affects home‐cage activity in rodents, however.…”
Section: Introductionmentioning
confidence: 99%